Review of controversies in management of non-benign meningioma. (September 2016) - Paldor, Iddo; Awad, Mohammed; Sufaro, Yuval Z.; Kaye, Andrew H.; Shoshan, Yigal
Highlights: Maximal safe resection should be the goal in operations for WHO Grade II meningioma. Post-operative irradiation is not warranted in Grade II meningioma after gross total resection. Post-operative irradiation is warranted in Grade II meningioma after subtotal resection. Radiation therapy should be given after resection of Grade III meningioma. No drug therapy has been proven to extend survival or progression free survival in patients with non-benign meningioma. Abstract: Meningiomas are one of the most common brain tumors. World Health Organisation (WHO) Grade II and Grade III meningiomas are grouped together as non-benign meningioma (NBM). There are several controversies surrounding NBM management, including the significance of extent of resection and the efficacy of post-operative radiation and drug treatment. We reviewed the literature to develop recommendations for management of NBM. The questions we sought to answer were: Does gross total resection (GTR) improve patient outcome? Is radiation therapy (RT) warranted after complete or after incomplete resection of NBM? What drug therapies have been proven to improve outcome in patients with NBM? We found that GTR improves outcome in WHO Grade II meningioma, and should be attempted whenever considered safe. GTR correlates less closely to outcome in Grade III meningioma compared to subtotal resection (STR). Extreme measures to completely resect Grade III meningioma are not warranted. RT following GTR of Grade II meningioma does not improve patient outcome, and may be reserved for recurrence. RT improves outcome following STR of Grade II meningioma. RT improves outcome after resection of Grade III meningioma. No drug therapy has been shown to improve outcome in NBM. This review elucidates recommendations for some of the controversies involving NBM.